Friday

March 27, 2015

March 27, 2015

Posted by **Alicia** on Sunday, November 18, 2007 at 10:04pm.

x(squared)+7x+10=0

(x+r)(x+s)

=x(squared)+sx+rx+rs

=x(squared)+(r+s)x+rs

x(squared)+(r+s)x+rs=x(squared)+7x+10

r+s=7

rs=10

(2)(5)=10 and 3+4=7

x(squared)+7x+10=(x+5)(x+2)

- College Algebra -
**Reiny**, Sunday, November 18, 2007 at 10:16pmyes, you are right,

For these kind of problems why don't you just expand your answer using FOIL to check if you are right?

**Answer this Question**

**Related Questions**

math - i am having a minor difficulty i've been stuck for over an hour and don't...

math - How do i find the area of a triangle? For example: A squared + b squared...

algebra 2 multiple choice HELP - find f(a), if f(t) = 2t2(squared)-t-2 A. 2(a+t)...

Math - Find the shortcut. Solve these problems. Then find and explain a shortcut...

10th Grade Algebra - Please help me with these factorise algebra questions!!! 1...

Algebra - i need to use the quadratic formula 2 solve these 4 questions: 1. x(...

Math11U - A Pythagorean Triple is a set of integers that satisfy the Pythagorean...

Math - I need help with this problem. In decimal form, write the ratio of the ...

algerbra - i have to simply the expression 3x squared-10+4x+8-x squared, so far ...

math - Factor (15a squared bc squared -9a squared b to the fourth c) by finding ...